Transferable tetracycline resistance in Clostridium difficile. - Smith, C J (1981)
The transfer of tetracycline resistance among strains of Clostridium difficile is described. Transfer occurred by a conjugation-like event that was insensitive to deoxyribonuclease, could not be mediated by donor culture filtrates or chloroform-treated donor cultures, and required cell-to-cell contact. Tetracycline-resistant progeny recovered from matings displayed a resistance phenotype identical to that of the donor in level of resistance, constitutive expression, and transmissibility. Although the original tetracycline-resistant donor contained 5 x 10(6)- and 22 x 10(6)-dalton plasmids, standard physical analyses of antibiotic-resistant transconjugants revealed no plasmid deoxyribonucleic acid molecules in common with the donor strain. Furthermore, tetracycline-susceptible derivatives of the original donor always possessed a plasmid complement identical to that of the resistant parental strain as determined by restriction endonuclease digestion analysis. The results indicate that the tetracycline resistance determinant(s) was not encoded by readily detectable plasmid deoxyribonucleic acid and may be chromosomally located.